Home, school, and community factors on Indonesian secondary students’ self-identity changes - Harjanto, Ignatius; Lie, Anita; Wijaya, Juliana (Indonesian Journal of Applied Linguistics, 2019)
This study examines the effects of home, school, and community factors on Indonesian secondary students’ self-identity changes in relation to their use of English. The subjects of this research were 1707 Indonesian high school students from four big cities in Indonesia. The instrument was a questionnaire on the influence of English exposure at home, school, and community and six categories of self-identity changes: self-confidence, subtractive, additive, productive, split, and zero changes. The analysis showed that there were three noticeable findings, they were (1) the issue of self-identity change on Indonesian students was not evident, (2) the greatest influence on the six self-identity indicators came from community factors altogether although slightly, and (3) the biggest influence of all was home factors on the subjects’ self-confidence. A conclusion is then made with a recommendation.